Ketahanan enam galur padi sawah (Oryza sativa L) terhadap wereng batang coklat (Nilaparvata lugens Stí¥l) asal Patokbeusi, Subang : Resistance of six lowland rice lines (Oryza sativa, L .) to brown planthopper (Nilaparvata Lugens, Stí¥l.) from Patokbeusi, Subang - Triwidodo, Hermanu; Nurmansyah, Ali; Sartiami, Dewi; Amanatillah, Niky Elfa; Meliyana; Lukvitasari, Luna (Perhimpunan Entomologi Indonesia, 2023)
Release of new varieties requires qualitative as well as quantitative characters of the lines. For rice varieties, resistance to brown plant hopper (BPH) (Nilaparvata lugens, Stí¥l) (Hemiptera: Delphacidae) is an important character that should be tested. The purpose of this study was to determine the resistance of new rice lines of rice cultivar to BPH. In this study, the tests were carried out on 6 (six) lines of candidate varieties developed by IPB University, namely TCIPB202101, TCIPB202102, TCIPB202103, TCIPB202104, TCIPB202105, and TCIPB202106. Resistance to BPH assays was conducted by screening and population development tests. Inpari 30 and Ciherang varieties were used as controls. The results showed that the TCIPB202106 line is the most resistant to BPH attack, while the TCIPB202103 line is the most susceptible to BPH attack. The average number of nymphs in the TCIPB202106 line was three times lower than those in Inpari 30 and Ciherang. The results of the population growth test were in line with the results of the screening test which indicated that the TCIPB202106 line is classified as moderately resistant to BPH.